Sustainable of Environment and Green Technology Financing from the Shariah Law Perspective: (Kelestarian Alam Sekitar dan Pembiayaan Teknologi Hijau dari Perspektif Undang-undang Syariah) (Kanun: Jurnal Undang-undang Malaysia, 2014)
This writing is to discuss the relationship between the concept of environmental sustainability, green energy and green technology from the perspective of Islamic law. Islamic financing green technology is a challenge for the financial industry. Qualitative methods and approaches in harmonization of legislation have been adopted in which the principles of Shariah law have been harmonized with prinisp conventional financing and the environment. The results show that environmental sustainability and technology elements that are interrelated and can be realized in the preservation and conservation of the environment. Thus, creating a green -based technology is seen as an effort and contribution to the environment. Finally, Islamic finance is an ideal instrument to promote green energy and environmental sustainability.Keyword: sustainability, environment, green technology, green technology financing.